Morphofunctional changes and their implications on the masticatory function of senescent elderly (Research, Society and Development, 2024)
Aim: to analyze the impact of morphofunctional changes on mastication in senescent elderly people. Methodology: The functionally independent senescent elderly underwent an interview that addressed respiratory, eating and oral habits, as well as an assessment of morphological characteristics, posture, tonicity, mobility and functions of the stomatognathic system. Data were stored in the e-myo software. This research was approved by the Research Ethics Committee and carried out between 2017 and 2019. Results: 85 individuals participated, most of them female aged between 60-79 years. The majority presented alterations in mastication with frequent presence of more than one characteristic in the same volunteer. The masticatory rhythm tends to be slowed down and compensations are frequent due to anatomical changes and dental conditions of the volunteers. The increased use of the perioral muscles and vertical movements of the mandible during the performance of the function by the long-lived were frequent. Decreased tongue mobility had an influence on masticatory function, which differed from tonicity, making the use of isotonic exercises pertinent. However, the self-perception of this public often does not match the conditions presented, requiring greater care on the part of professionals. Conclusion: the loss of more than twenty teeth, the reduced mobility of the tongue and the increased participation of the perioral muscles influenced the changes in mastication of the sample studied.